Kantasaamen sensiivisen *-kše̮-johtimen kehityksestä ja edustuksesta nykysaamessa - Koponen, Eino; Kuokkala, Juha (Nordlyd, 2022)
The article discusses Saami censive verbs containing the suffixal element -š-, such as North Saami guhkášit ‘consider (too) long’ (of guhkki ‘long’). The occurrence of individual derivatives and derivational subtypes across the Saami languages are studied on the basis of extensive dictionary data, and the outlines of the historical development of the derivational type are sketched. Considering the Inari Saami verbs of type viššâlšukšâđ ‘consider diligent’ and data from past centuries, it is argued that the derivational type goes back to Proto-Saami *-kše̮-, which, in turn, is a loan suffix from Finnic (cf. Finnish kummeksua ‘find something odd’ ← kumma ‘odd’, halveksia ‘despise’ ← halpa ‘cheap’).